REVOLUTIONIZING LAST-MILE DELIVERY: THE INTEGRATION OF GENERATIVE AI AND MULTIMODAL LEARNING - Abdul Muqtadir Mohammed , (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
This article explores the transformative impact of integrating generative AI and multimodal learning technologies in last-mile delivery operations. It examines how the combination of Large Language Models, Vision-Language Models, and Geospatial Foundation Models addresses critical challenges in urban logistics, including address accuracy, route optimization, and resource allocation. The article demonstrates significant improvements in operational efficiency, environmental sustainability, and customer satisfaction through AI-driven solutions. The article includes a comprehensive case study of implementation in major metropolitan areas, highlighting the practical benefits of autonomous vehicles and IoT integration. The article further explores future implications, focusing on predictive analytics, enhanced automation, and sustainable delivery options, providing valuable insights for organizations seeking to optimize their last-mile delivery operations.